First glacier-vibroseismic experiment: results from cold firn of Colle Gnifetti - Polom, Ulrich; Hofstede, Coen; Diez, Anja; Eisen, Olaf (Near surface geophysics, 2014)
In the summer of 2010, a small shallow reflection seismic experiment was carried out on the firn covered cold glacier of Colle Gnifetti, Monte Rosa group, Swiss/Italian Alps. At this site, the physical properties of ice are comparable to polar conditions, which is why this site is often used for methodological tests. The experiment at 4500 m elevation was designed to explore the scope of shallow vibroseis for seismic targets within and below the glacier. A small ELVIS vibrator system was used to generate shear waves and compression waves for SH- and P-wave receiver setups of two profiles. The resulting sections clearly show a boundary from ice to rock around 60 m and deeper structures below the glacier. The deepest features are estimated to be 150 m for the SH-waves and 220 m for the P-waves. Reflections could be detected also within the ice overburden, which are preliminarily interpreted as a change of density in the upper 30 m and possibly crystal orientation fabric in the ice column. Furthermore, elastic parameters could be derived from seismic velocities, due to clear basement reflections. The results of this unique experiment enable new insights into the internal structure of ice masses and open a promising new investigation method for sub-ice structures and properties, such as basal sediments.
First published: 01 June 2013
Gesehen am 08.09.2020